Comparison of Bio-Based Triboelectric Nanogenerator (B-TENG) Performance for Self-Powered Sensor Applications - Saparin M.A.; Salleh H.; Hen C.K.; Kumar S. (Institute of Electrical and Electronics Engineers Inc., 2024)
The objective of the paper is to investigate the mechanical-electrical conversion properties of biomaterials as a layer in the Bio-Based Triboelectric Nanogenerator (B-TENG), and characterize the output performance for a self-powered sensor system. The main focus of the B-TENG design is on material and structural modifications. The experiments were conducted to compare the output of the B-TENG using wood paper as the base with the bio-material soft wood and coconut husk. The PTFE was used as a control experiment. The triboelectricity method used in this work was the sliding rotational mode. The B-TENG design uses a circular vane with overall diameter of 100 mm. The measurements were taken for different number of vanes (3, 4, and 5) at a range of 200 rpm to 1400 rpm. The maximum open circuit voltage output was at 1400 rpm, with a range between 2.57 V (coconut husk) to 4.12 V (softwood). The highest output was from the combination of wood paper and softwood. It is recommended that the performance can further be improved by including more number of vanes and other type of bio-based material. 2023 IEEE.